Pyrrole‐based pincer ligands containing iminophosphorane moieties and their coordination chemistry with group 1 metals and magnesium. Issue 14 (7th May 2021) - Ehrlich, Nico; Freytag, Matthias; Raeder, Jan; Jones, Peter G.; Walter, Marc D.
Abstract: The Staudinger reaction of 2, 5‐bis((di‐ tert ‐butylphosphaneyl)methyl)‐1 H ‐pyrrole ( t Bu PNP)H; t Bu PNP=C4 H2 N‐2, 5‐CH2 P t Bu2 ) with 2 equiv. of Me3 SiN3 cleanly furnishes 1, 1′‐((1 H ‐pyrrole‐2, 5‐diyl)bis(methylene))bis(1, 1‐di‐ tert ‐butyl‐ N ‐(trimethylsilyl)‐λ 5 ‐phosphanimine) (1 ; (NPNPN)H, NPNPN=C4 H2 N‐2, 5‐CH2 P t Bu2 NSiMe3 ) in excellent yield. Pyrrole 1 is easily deprotonated by alkali metal amides, [MN(SiMe3 )2 ] (M=Li, Na, K, Cs) to yield the corresponding alkali metal pyrrolides, 1‐M . Compound 1‐Li is features a κ‐ N, N, N coordination whereby both iminophosphorane side‐arms are coordinated to the lithium cation (with additional short Li⋅⋅⋅H contacts, whereas the heavier congeners form dimeric structures. This results in κ‐N, N coordination within one [(NPNPN)M] (M=Na, Cs) unit, and the dimeric structure is then completed by additional η 5 ‐coordination of the pyrrolyl ligand to the neighbouring alkali metal. Furthermore, heteroleptic magnesium alkyl complexes, 1‐MgR, are isolated from the reaction of [MgR2 ] (R= CH2 SiMe3, CH2 CMe3, CH2 CMe2 Ph) with (PNP*)H (1 equiv). Abstract :